Definition of a motor oil change interval for high-volume diesel engines based on its current characteristics assessment - Sejkorová, Marie; Hurtová, Ivana; Glos, Josef; Pokorný, Jan (My University, 2017)
Evaluation of motor oils is given a big attention due to a fact that during the years it was proven that lubrication is a key factor influencing a service life of vehicles and industrial engines. Motor oil must fully serve in various operational conditions (such as city traffic with frequent braking and acceleration) as well as in different climatic conditions (arctic winters or tropical summer heat). Therefore, the change of the motor oil should be optimized in order to ensure proper engine efficiency and extend its service life. The article presents result of testing of two types of used motor oils with the same specification ACEA E4/E7, SAE 10W.40, from two different suppliers. These oils were used in a high.volume diesel engine of IVECO CITY BUS. The sales representatives recently offered a more expensive motor oil (in the text marked oil B) claimed that in their oil can extend the change interval from 40,000 km to 80,000 km. Evaluation of selected parameters did not prove that after exceeding of change interval 40,000 km, the more expensive motor oil would ensure all required functions as it had been declared by the supplier's sales representative.
Nastavení výměnného intervalu motorového oleje pro velkoobjemové vznětové motory na základě stanovení jeho aktuálních charakteristik
Keywords: change interval; degradation; emission spektrometry; FTIR spektrometry; lubricant analysis; lubricant quality; measurement; motor oil; particles analysis; výměnný interval; degradace; emisní spektrometrie; FTIR spektrometrie; analýza maziva; kvalita maziva; motorový olej; analýza částic